Successful catheter cryoablation for atrial fibrillation in patients with permanent cardiac pace-maker implants - Güneş, Hacı Murat; Babür Güler, Gamze; Demir, Gültekin Günhan; Kılıçaslan, Fethi (Sağlık Bilimleri Üniversitesi, Kartal Koşuyolu Yüksek İhtisas Eğitim ve Araştırma Hastanesi, 2018)
In daily practice, several methods including electrocardiography, 24-hour Holter ECG monitoring, or event recorders are frequently used for diagnosis and follow-up of patients with atrial fibrillation (AF). Although these tests provide crucial information, they may be insufficient in selected cases. In this case, we utilized intracardiac electrocardiogram recordings for both diagnosis of AF and detection of its recurrence in a patient with a permanent pace-maker who underwent AF ablation because of symptomatic and asymptomatic paroxysmal AF episodes. Because patients with permanent pacemakers are continuously monitored via intracardiac recordings, we believe that it is the most definite method for both diagnosis and monitoring of treatment success.

Günlük pratikte hastalarda atriyal fibrilasyon ataklarının tanı ve takibinde sıklıkla elektrokardiyografi, ritim holter ve olay kaydedici kullanılmaktadır. Bu testler önemli bilgi sağlasa da yetersiz kaldıkları olgular olabilmektedir. Biz olgumuzda daha önce kalıcı kalp pili implante edilmiş, semptomatik ve asemptomatik atriyal fibrilasyon atakları olan hastanın tanısının koyulmasında ve atriyal fibrilasyon ablasyonu sonrası rekürrensin takibinde kalp içi kayıtlardan faydalandık. Kalıcı kalp pili olan hastalarda, intrakardiyak kayıtlarla devamlı takip sağladığından, hem tanı koymada hem de tedavi başarısını belirlemede kullanılabilecek en kesin yöntem olduğunu düşünüyoruz.
Kalıcı kalp pili implantı olan atriyal fibrilasyonlu hastada başarılı kateter kriyoablasyon
Keywords: Atrial Fibrillation Ablation; Intracardiac Recordings; Atriyal Fibrilasyon Ablasyonu; İntrakardiyak Kayıtlar